LOGICO-SEMANTIC RELATIONS IN A UNIVERSITY STUDENT'S ARGUMENTATIVE ESSAY: CONTENT ANALYSIS OF CLAUSE COMPLEXES - Hitimala, Hardianto; Gunawan, Wawan (Universitas Muhammadiyah Metro, 2026)
An argumentative essay is one of the most difficult types of writing for university students, especially in constructing sentences that are logical, cohesive, and coherent, which is called a logico-semantic relation in systematics functional linguistics (SFL). Thus, the objective of this research was to find out the logico-semantic relations manifest in the argumentative essays crafted by university students and a teacher's perspectives on the use of logico-semantic relations in students’ writing. The analysis showed that the essay comprised 10 clause complexes and exhibited logico-semantic relations, as evidenced by the identification of expansion and projection relations. The data on expansion relation revealed that out of 10 clause complexes, 5 clauses 50% had elaboration relations, 3 clauses 30% had enhancement relations, and 2 clauses 20% had extension relations. Among 10 clauses, 3 belonged to the category of idea projection marked by words such as “debate, find out, thinking, based on”, while 2 belonged to the category of locution projection marked by words “tell, say”, and the remaining two clauses did not belong to any category of projection. Concerning the interview, the teacher possessed a solid comprehension of the concept of logico-semantic relations, which are the techniques of linking clauses or sentences to convey the logical and semantic meanings of the text. The teacher also emphasized the importance of logico-semantic relations for attaining cohesion and coherence in academic writing.